Outcome of internal fixation procedure: miniplate vs cross K wires for displaced metacarpal metaphyseal fracture - Shair, Naveed Ali; Tariq, Abdullah; Shakeel, Muhammad; Kashif, Muhammad; Ahmad, Ejaz; Abubakar, Muhammad (International Journal of Research in Medical Sciences, 2020)
Background: Metacarpal fractures are considered a frequent orthopedic injury seen commonly in emergency units. Objectibe of thestudy was to compare the outcome of internal fixation procedure of miniplate versus cross kirschner wires (k-wires) for displaced metacarpal metaphyseal fractures. Methods: In this experimental prospective study, 100 patients with metacarpal metaphyseal fracture were considered. internal fixation was done by miniplate in one group and cross k wires in other group. Outcomes in terms of radiological union were compared between both groups. The data was analyzed by using SPSS for windows (version 26.0). Results: Mean age of the patients was 38.70±13.61 years. Male to female ratio of the patients was 1.2:1. The radiological success was noted in 76 (76.0%) patients. Statistically insignificant difference was found between the study groups in terms of radiological success of the patients (p=0.6396). K wire fixation was recorded to have significantly shorter duration of operation time in comparison to miniplate fixation (p=0.0001). Conclusions: The internal fixation procedure of both miniplate and k wire are equally effective in terms of radiological success for management displaced metacarpal metaphysis fractures. As compared to miniplate fixation, K wire fixation was found to have significantly shorter duration of operation time.